2021
DOI: 10.9758/cpn.2021.19.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ulinastatin and Sulforaphane Alone or in Combination in Rat Model of Streptozotocin Diabetes Induced Vascular Dementia

Abstract: Objective: Vascular Dementia (VaD), is associated with metabolic conditions. Diabetes is a major risk factor for the development of VaD. This study investigates the efficacy of ulinastatin (UTI) and sulforaphane (SUL) in streptozotocin (STZ)-diabetes induced vascular endothelium dysfunction and related dementia. Methods: Single dose STZ (50 mg/kg i.p.) was administered to Albino Wistar rats (male, 200−250 g). Morris water maze and attentional set shifting tests were used to assess the spatial learning, memory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 78 publications
(193 reference statements)
1
1
0
Order By: Relevance
“…Nevertheless, a limited number of studies have investigated the prophylactic effects of SFN on the cholinergic system. Generally, our results match those that support the evidence of SFN's potential effects on the improvement of the cholinergic system, thus improving learning and memory [24,75]. For instance, in mouse models of scopolamine-induced memory impairment, the administration of SFN (10 or 50 mg/kg) to C57BL/6 mice via oral gavage for 2 weeks significantly reduced AChE activity in the frontal cortex [24].…”
Section: Prophylactic Effect Of Sfn Against Ache Overactivation Induc...supporting
confidence: 89%
“…Nevertheless, a limited number of studies have investigated the prophylactic effects of SFN on the cholinergic system. Generally, our results match those that support the evidence of SFN's potential effects on the improvement of the cholinergic system, thus improving learning and memory [24,75]. For instance, in mouse models of scopolamine-induced memory impairment, the administration of SFN (10 or 50 mg/kg) to C57BL/6 mice via oral gavage for 2 weeks significantly reduced AChE activity in the frontal cortex [24].…”
Section: Prophylactic Effect Of Sfn Against Ache Overactivation Induc...supporting
confidence: 89%
“…Previous research on the effect of UTI on blood glucose levels has yielded conflicting results. Sharma et al found that UTI had no significant effect on hyperglycemia in STZ-induced DM [ 32 ], whereas Zhao et al found that UTI administration improves stress-induced hyperglycemia by reducing inflammation and improving insulin resistance [ 46 ]. These controversies could be explained by different models used in different studies.…”
Section: Discussionmentioning
confidence: 99%